Effects of Cigarette Smoking on Transplant Survival: Extending or Shortening It? - Qiu, Feifei; Fan, Ping; Nie, Golay D.; Liu, Huazhen; Liang, Chun-Ling; Yu, Wanlin; Dai, Zhenhua (Frontiers in Immunology, 2017)
Cigarette smoking (CS) regulates both innate and adaptive immunity and causes numerous diseases, including cardiovascular, respiratory, and autoimmune diseases, allergies, cancers and transplant rejection. Therefore, smoking poses a serious challenge to the healthcare system worldwide. Epidemiological studies have always shown that CS is one of the major risk factors for transplant rejection, even though smoking plays redundant roles in regulating immune responses. The complex roles for smoking in immunoregulation are likely due to molecular and functional diversities of cigarette smoke components, including carbon monoxide (CO) and nicotine. Especially, CO has been shown to induce immune tolerance. Although CS has been shown to impact transplantation by causing complications and subsequent rejection, it is overlooked whether CS interferes with transplant tolerance. We have previously demonstrated that cigarette smoke exposure reverses long-term allograft survival induced by costimulatory blockade. Given that CS impacts both adaptive and innate immunity and that it hinders long-term transplant survival, our perspective is that CS impacts transplant tolerance. Here we review impacts of CS on major immune cells that are critical for transplant outcomes, and propose the cellular and molecular mechanisms underlying its effects on alloimmunity and transplant survival. Further investigations are warranted to fully understand why CS exerts deleterious rather than beneficial effects on transplant survival even if some of its components are immunosuppressive.